From coping strategy to hopeful everyday practice: Changing interpretations of food self‐provisioning. Issue 3 (28th July 2022) - Daněk, Petr; Sovová, Lucie; Jehlička, Petr; Vávra, Jan; Lapka, Miloslav
Abstract: While alternative food networks (AFNs) have become the leading conceptualisation of sustainable food systems, vibrant scholarship on food self‐provisioning (FSP) in Central and Eastern Europe has remained confined to the geopolitical region it investigates. This article brings these two bodies of thought closer together in two steps. First, we trace four framings of FSP deployed over the last three decades—coping strategy, cultural practice, hobby and source of good food and reading FSP as transformative practice—to demonstrate its progressive affinity with AFNs. Second, we follow the most recent framing in highlighting the material reality of local food production as a feature shared by both FSP and AFNs. From this perspective, FSP can be understood as a more radical variant of AFNs given its more substantial environmental and social impact (FSP is more widespread and socially inclusive and less dependent on market transactions). By uncovering the epistemological underpinnings of these different framings of FSP and exploring their implications for food practices on the ground, this article draws general lessons for scholarship aiming to advance food system transformation.